Prevalence of diabetes in glaucoma. Issue 6488 (13th July 1985) - Mapstone, R; Clark, C V
Abstract : Oral glucose 75 g was given to 352 patients with chronic glaucoma, acute glaucoma, or ocular hypertension and 73 patients without glaucoma. The proportion of patients with shallow anterior chambers who showed an abnormal response was significantly greater than that in patients with deep anterior chambers and in the control group (p less than 0.005). The probability of developing an abnormal response to oral glucose tests increased as the depth of the anterior chamber decreased; these two variables showed a significant negative linear correlation (r = -0.79, p less than 0.001). The high prevalence of autonomic dysfunction in patients with shallow anterior chambers and glaucoma may explain this association. Because of this, acute glaucoma should be regarded as a symptom of diabetes.